PENGARUH PROGRAM FACTORY VISIT DAN FILM SHOWING TERHADAP PEMBENTUKAN BRAND IMAGE PADA PT YAKULT INDONESIA PERSADA CICURUG SUKABUMI - Ray Sinta Rahayu; Lucky Hikmat Maulana (Fakultas Ekonomi Universitas Djuanda, 2016)
The purpose of the research is to determine the response of visitors to the factory visit program conducted in PT Yakult Indonesia Persada, to determine the response of participants to the program showing the film held in PT Yakult Indonesia Persada and the response of visitors and participants of the brand image of PT Yakult Indonesia Persada, and to know influence factory visit program and showing films simultaneously and partially to the formation of brand image on PT Yakult Indonesia Persada. The population in this study were the visitors and participants factory visit programs and movies showing PT Yakult Indonesia Persada in april 2015. The sampling of 120 people were taken from both programs. Analysis of data using multiple linear regression analysis, the correlation coefficient, coefficient of determination, F test and t test using SPSS 19. The results showed that the response of visitors and participants of the two programs are very good and the response to any good brand image, as well as simultaneous program factory visit and films showing positive and significant impact on the formation of brand image and partially each factory visit programs and movies showing positive and significant impact on the formation of brand image PT Yakult Indonesia Persada.Keywords: Factory visit, Film showing and Brand image.